Siamese twin pregnancy in peritoneal dialysis : first case in the world - D El Hamssili; T. Bouattar; R. Bayahia; L. Benamar (RDPLF, 2018)
Introduction: The probability of conception is low in peritoneal dialysis (PD), and the probability of successful pregnancy is even lower. Nearly 60 years after the first reported case of successful pregnancy in a dialysis patient, many questions about pregnancy during dialysis remain unresolved, namely the required dialysis dose, the follow-up rhythm, the choice of the the most appropriate dialysis technique. Case report: We report the first case worldwide of twin Siamese pregnancy in a patient on continuous ambulatory peritoneal dialysis (CAPD). The pregnancy was diagnosed at 7 weeks of amenorrhea (WA). The patient was initially under 2 exchanges per day, with 2-liter bags of Dianealof 1.36% glucose. As soon as the pregnancy was discovered, the prescription was modified, putting the patient under 3 exchanges a day with the same concentrates. The infusion volume was maintained at 2 liters up to 18 WA , and then reduced to 1.5 liters due to patient discomfort and abdominal hyperpressure. Daily ultrafiltration ranged from 180 to 800 ml with 1 liter diuresis. The blood pressure was well controlled, with an average of 125/80 mmHg, without need of  antihypertensive drugs. On a biological level, the Kt / V was 2.2, nPCR was 0.8, and the weekly clearance was 80 L / 1.73 m². The average hemoglobin was 11.5 g / dl under erythropoietin 9000 units per week. At 20 WA, obstetrical ultrasound revealed a mono-chorionic, mono-amniotic twin pregnancy. Due to high maternal and fetal risks, closer obstetrical control was indicated. At 24 WA, morphological obstetrical ultrasound coupled with Doppler examination of the uterine and umbilical arteries favored the diagnosis of mono-amniotic mono-chorionic twin pregnancy with strong suspicion of Siamese contiguous to the pelvis, with a cerebral malformation in one of the fetuses. The patient experienced intense contractions and pelvic pain leading to an emergency cesarean section with two surviving Siamese twins, contiguous to the pelvis, weighing 900g, but who died one day after delivery. Conclusion: Pregnancy during dialysis is at high maternal and fetal risks. It is necessary to prepare and follow this pregnancy to optimize the chances of success. This implies an adaptation of the medical treatment and dialysis prescription, including the volume and modality of exchanges. The same holds true for gynecological and obstetrical follow-up, which must be regular and strict, in order to prevent any maternal-fetal complications.